Pemberdayaan Remaja Balung Lor dalam Pengembangan Aset UMKM melalui Workshop Manajemen Bisnis Dasar oleh Mahasiswa KKN UIN KHAS Jember Kelompok 24 - Diyanatil Azkiya; Shabrina Hulyati; Irza Nur Oktavia; Muhammad Is’adur Rofik; Elok Hadia Putri; Putra Andika; Ahmad Syauqi Taajul Islam; Rachmatia Aura Amanda; Izmi Nazifah Khairunnisa; Rio Setiawan; Fitri Faissatul Laili (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
The program “Youth Empowerment in Developing UMKM Assets through a Basic Business Management Workshop in Balung Lor Village” aims to address the low involvement of youth in the village’s micro-business sector, which is currently dominated by elderly entrepreneurs. This community service initiative applies the Asset-Based Community Development (ABCD) approach using observation, interviews, focus group discussions, and community asset mapping. The theoretical framework of asset-based empowerment positions youth as a crucial human asset for economic regeneration. The discussion highlights entrepreneurial mindset building, basic business literacy, digital marketing skills, and youth creativity in generating new economic initiatives. The results show significant improvement in youth understanding of production costing, capital management, business planning, and social media-based promotion. In conclusion, the ABCD approach effectively enhances youth participation in local economic development, strengthens UMKM sustainability, and lays a solid foundation for creating a future generation of adaptive and innovative village entrepreneurs.